Jakob Kolding : Posters. - Massey, Doreen; Exhibition. Jakob Kolding : Posters. Centre d'édition contemporaine Genève. 2003-03-28. 2003-05-10 (2003)
This briefcase, including 18 folded prints, is gathering reproductions of some last posters, streetview photographs of the posters, several texts in french and/or in english ; an artist introduction, a text about tree past poster's projects, a text of Doreen Massey (geographer).
This publication is published on the occasion of Jakob Kolding's exhibition at the Centre d'édition contemporaine, Geneva, from March 28 to May 10, 2003
Engels
Frans
boek
Keywords: Kolding, Jakob